Ensino de falácias através do jogo “Não seja enganado!” - Caetano, Camilla Keilhany de Sousa (2024)
The teaching of philosophy in high school faces significant challenges. One of these challenges is the difficulty of addressing abstract and conceptual topics, such as logical fallacies, which are errors in reasoning frequently present in everyday arguments. This study analyzes the construction of arguments and their role in the development of critical thinking, evaluating the game “Não Seja Enganado!” as a pedagogical tool. Based on authors such as Copi, Mortari, Walton, Carnielli, and Epstein, the research combines a literature review and empirical research. Thus, we present concepts of linguistic logic and 18 categories of fallacies; digital traps, such as filter bubbles and fake news, and the importance of critical thinking in the contemporary context; and the challenges in teaching philosophy, considering the contemporary context and the New High School curriculum. The use of playfulness in teaching is also explored, with a focus on the game developed in the 2019 Pedagogical Residency project at UFC. The research, with a qualitative and quantitative approach, was conducted between 2023 and 2024 with two groups: high school students from the state public network and adults with different levels of education. The results indicate that 82.2% of participants considered that the game facilitated their understanding of the topic, demonstrating its viability as a pedagogical tool for teaching fallacies. In addition to the research, this work concludes by leaving, as an educational product, the compilation of the 190 examples of fallacies used in the game, analyzed and discussed, to inspire students of the subject in creating and reflecting on their own arguments.